BRCA1 and BRCA2 deficient tumour models generate distinct ovarian tumour microenvironments and differential responses to therapy - Farokhi Boroujeni, Salar; Rodriguez, Galaxia; Galpin, Kristianne; Yakubovich, Edward; Murshed, Humaira; Ibrahim, Dalia; Asif, Sara; Vanderhyden, Barbara C. (Journal of ovarian research, 2023)
Clinical trials are currently exploring combinations of PARP inhibitors and immunotherapies for the treatment of ovarian cancer, but their effects on the ovarian tumour microenvironment (TME) remain unclear. Here, we investigate how olaparib, PD-L1 monoclonal antibodies, and their combination can influence TME composition and survival of tumour-bearing mice. We further explored how BRCA deficiencies can influence the response to therapy. Olaparib and combination therapies similarly improved the median survival of Brca1 - and Brca2 -deficient tumour-bearing mice. Anti-PD-L1 monotherapy improved the survival of mice with Brca1- null tumours, but not Brca2- null tumours. A detailed analysis of the TME revealed that olaparib monotherapy resulted in a large number of immunosuppressive and immunomodulatory effects in the more inflamed Brca1- deficient TME but not Brca2- deficient tumours. Anti-PD-L1 treatment was mostly immunosuppressive, resulting in a systemic reduction of cytokines and a compensatory increase in PD-L1 expression. The results of the combination therapy generally resembled the effects of one or both of the monotherapies, along with unique changes observed in certain immune populations. In-silico analysis of RNA-seq data also revealed numerous differences between Brca- deficient tumour models, such as the expression of genes involved in inflammation, angiogenesis and PD-L1 expression. In summary, these findings shed light on the influence of novel therapeutics and BRCA mutations on the ovarian TME.